(3GdefgL GdeHjf aj eHGMK GdCQHYjf aj CUhd GdOjfs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi hLH dLdGdg GdEJUGa HUaGJ GdLdGd hGdceGd hHYO adeG cGf GdYde GdcdGei CUd GdYde GdTQYi hGdabg GdeYi HOdjd GfJgi GdYdhe GdTQYjI ai SdSdI GdeHGMK SejfGgG HGdefgL GdeHjf ai eHGMK GdCQHYjf s
(3BNQgG (B:s
(3hdG JaQM ai eHGMKGJ Phi GdJMUjd aEfgG efGbTI LOdjI dGeDGNQI YbdjI ced hGdMeO ddg Mb MeOg hUdi Gddg Ydi SjOfG eMeO fHjg hYHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3hgh CLhHg Ydi GYJQGVGJ bO JQO Ydi GdHGMKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(676/1) s
Keywords: (3CUhd Gdabgs